Composition and spatio-temporal changes in mesozooplankton diversity and density in an Amazonian estuary (Emboraí Velho, Pará, Brazil) - Barros, Francisco Alex Lima; de Andrade, Marcela Pimentel; Silva, Thaynara Raelly da Costa; Pereira, Luci Cajueiro Carneiro; da Costa, Rauquírio Marinho (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2019)
The present study investigated the effect of precipitation on hydrological components and their impacts on the mesozooplankton community in the Emboraí Velho estuary, northern Brazil. Nycthemeral samplings were performed with 200 μm mesh plankton nets. The Emboraí estuary showed a predominance of turbid, well-oxygenated mesohaline and euhaline waters, with moderate concentrations of chlorophyll-a and high temperatures. Mesozooplankton was composed of a total of 27 species, highlighting Acartia lilljeborgi, with abundances up to 2,708 ± 4,955 ind.m-3, and Oikopleura dioica (745 ± 1,280 ind.m-3), both at station E1, in November. Paracalanus quasimodo (559 ± 828 ind.m-3) and Pseudodiaptomus richardi (429 ± 713 ind.m-3) showed higher abundances at E1 station in April. Oithona hebes (247 ± 327 ind.m-3) and Euterpina acutifrons (339 ± 677 ind.m-3) showed the highest values at station E1 in November, while Pseudodiaptomus marshi (130 ± 230 ind.m-3) and Oithona oswaldocruzi (56 ± 97 ind.m-3) presented higher abundances in November and August, respectively, at this same station. The alternation of dominance of the identified species was determined by their tolerances to variations in salinity, availability of autotrophic food sources (chlorophyll-a), and recruitment rates.
Keywords: Amazonian coast; Coastal plankton; Precipitation; Environmental variables